Wanita, Keluarga dan Hak Asasi Manusia dalam Islam - Zaenal Arifin; Moh. Romli (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2024)
There are two relationship among three elements of woman, household ang human right in Islam. First relationship reflecting the woman between household and carrier. A woman (wife) has right and opportunity to realize her carrier with on necaligence of function and consequences (in household) as also man/husband is obliged to carry on his function as social people/member who permanently paying attention to function of his family/household. Furthermore, second relationship reflecting the woman with her human right such as no difference of man and woman are merely to worship Allah. Almighty, right to divorce husband and the others relating to the human right.